Near-infrared triple-helical peptide with quenched fluorophores for optical imaging of MMP-2 and MMP-9 proteolytic activity in vivo - Zhang, Xuan (Bioorg Med Chem Lett, 2014)
The gelatinase members of the MMP family have consistently been associated with tumor invasiveness, which make them an attractive target for molecular imaging. We report new activatable proteolytic optical imaging agents that consist of triple-helical peptide (THP) conjugates, with high specificity to the gelatinases, bearing quenched cypate dyes. With quenching efficiencies up to 51%, the amplified fluorescence signal upon cypate(3)-THP hydrolysis by the gelatinases (k(cat)/K(M) values of 6.4 × 10(3) M(−1) s(−1) to 9.1 × 10(3) M(−1) s(−1) for MMP-2 and MMP-9, respectively) in mice bearing human fibrosarcoma xenografted tumors was monitored with fluorescence molecular tomography. There was significant fluorescence enhancement within the tumor and this enhancement was reduced by treatment with pan-MMP inhibitor, Ilomastat. These data, combined with the gelatinase substrate specificity observed in vitro, indicated the observed fluorescence at the site of the tumor was due to gelatinase mediated hydrolysis of cypate(3)-THP.